2019
DOI: 10.1002/ppul.24435
|View full text |Cite
|
Sign up to set email alerts
|

Spanish multicentre study on morbidity and pathogenicity of tracheal bronchus in children

Abstract: Tracheal bronchus (TRB) has been generally considered an anatomical variant of the tracheobronchial tree without a precise pathological effect. Its prevalence is estimated to be between 0.2% to 3% of all children undergoing bronchoscopy and scientific information has been limited to case reports or small case series. Our working hypothesis was that TRB could trigger by itself recurrent or persistent respiratory symptoms. The objective of this retrospective and multicentre study of children with a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
(60 reference statements)
0
23
0
1
Order By: Relevance
“…A tracheal bronchus, also known as pig bronchus or “bronchus suis,” is defined as an anatomical variation in which an aberrant or additional bronchus originates from the supracarinal trachea. It is predominantly seen on the right side and has an estimated incidence of 0.06%–1.06% 46 . A tracheal bronchus is often asymptomatic and, therefore, reported prevalence rates in literature might underestimate the exact prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A tracheal bronchus, also known as pig bronchus or “bronchus suis,” is defined as an anatomical variation in which an aberrant or additional bronchus originates from the supracarinal trachea. It is predominantly seen on the right side and has an estimated incidence of 0.06%–1.06% 46 . A tracheal bronchus is often asymptomatic and, therefore, reported prevalence rates in literature might underestimate the exact prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in a cohort study on children with respiratory complaints requiring flexible laryngotracheobronchoscopy, tracheal bronchus was seen in 21% of DS children compared with 2.1% in non‐DS controls 41 . Furthermore, a recent multicenter study on tracheal bronchus showed that 11/113 (8.3%) children with tracheal bronchus had DS 46 . As far as the affected side is described, all but one article on tracheal bronchus in DS concerned right‐sided tracheal bronchus.…”
Section: Resultsmentioning
confidence: 99%
“…14 Three 2019 papers addressed other abnormalities of airway branching -tracheal bronchus, bridging bronchus, and bronchogenic cyst. Moreno et al 15 reported on 133 pediatric patients with tracheal bronchus from 13 institutions across Spain. This anomaly occurs when the right upper lobe bronchus arises from the trachea, or less commonly, the carina.…”
Section: Anatomic Lung Airway and Vascular Malformationsmentioning
confidence: 99%
“…Tracheal bronchus, in which the right upper lobe directly originates from the trachea, is not a rare condition. Its prevalence has recently been estimated to 0.2–3% of children undergoing bronchoscopy [2]. In most cases, it is found incidentally and is thus considered as a variant of the normal tracheobronchial anatomy [3].…”
Section: Diagnosis: Right-sided Pulmonary Isomerism With Bilateral Trmentioning
confidence: 99%